Projected Responses of Tidal Dynamics in the North Sea to Sea-Level Rise and Morphological Changes in the Wadden Sea - Jordan, Christian; Visscher, Jan; Schlurmann, Torsten (Frontiers in Marine Science, 2021)
This study explores the projected responses of tidal dynamics in the North Sea induced by the interplay between plausible projections of sea-level rise (SLR) and morphological changes in the Wadden Sea. This is done to gain insight into the casual relationships between physical drivers and hydro-morphodynamic processes. To achieve this goal, a hydronumerical model of the northwest European shelf seas (NWES) was set-up and validated. By implementing a plausible set of projections for global SLR (SLR_RCP8.5 of 0.8m and SLR_high-end of 2.0m) by the end of this century and beyond, the model was run to assess the responses of the regional tidal dynamics. In addition, for each considered SLR, various projections for cumulative rates of vertical accretion were applied to the intertidal flats in the Wadden Sea (ranging from 0% to 100% of projected SLR). Independent from the rate of vertical accretion, the spatial pattern of M2 amplitude changes remains relatively stable throughout most of the model domain for a SLR of 0.8m. However, the model showcases a substantial sensitivity towards the different rates of vertical accretion along the coasts of the Wadden Sea, but also in remote regions like the Skagerrak. If no vertical accretion is assumed in the intertidal flats of the Wadden Sea, the German Bight and the Danish west coast are subject to decreases in M2 amplitudes. In contrast, those regions experience increases in M2 amplitudes, if the local intertidal flats are able to fully keep up with the projected SLR of 0.8m. Between the different scenarios, the North Frisian Wadden Sea shows the largest differences in M2 amplitudes, locally varying by up to 14cm. For a SLR of 2.0m, the M2 amplitude changes are even more amplified. Again, the differences between the various rates of vertical accretion are largest in the North Frisian Wadden Sea (>20cm). Additionally, the local distortion of the tidal wave is significantly different between the scenarios. In the case of no vertical accretion, tidal asymmetry in the German estuaries increases, potentially leading to enhanced sediment import. Presented results have strong implications for local coastal protection strategies and navigation in adjacent estuaries.